2014
DOI: 10.1017/hpl.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

Bragg accelerator optimization

Abstract: We present the first steps of a design of the optimal parameters for a full Bragg X-Ray free electron laser (BX-FEL). Aiming towards a future source of coherent X-ray radiation, operating in the strong Compton regime, we envisage the system to be the seed for an advanced light source or compact medical X-ray source. Here we focus on the design of the accelerator parameters: maximum gradient, optimal accelerated charge, maximum efficiency, and 'wake coefficient', which relates to the decelerating electric field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Common to all various structures is the vacuum channel, where the electrons propagate, and the single TM 01 mode that accelerates them. Although preliminary results were previously presented for planar Bragg structures [20], for the numerical examples presented subsequently in this study, we adopt an azimuthally symmetric dielectric-loaded waveguide [21], as shown in Fig. 1, since it is possible to evaluate all the quantities of interest analytically.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common to all various structures is the vacuum channel, where the electrons propagate, and the single TM 01 mode that accelerates them. Although preliminary results were previously presented for planar Bragg structures [20], for the numerical examples presented subsequently in this study, we adopt an azimuthally symmetric dielectric-loaded waveguide [21], as shown in Fig. 1, since it is possible to evaluate all the quantities of interest analytically.…”
Section: System Descriptionmentioning
confidence: 99%
“…Previous studies [6,19,20] formulated the efficiency of accelerating single bunch (η 1 ) with a charge q in terms of three quantities: (i) the accelerating unloaded gradient generated by the laser ðE acc ¼ G 0 Þ; (ii) the wake coefficient (κ) which by virtue of linearity of Maxwell's equations relates the decelerating electric field that acts on the bunch ðE wake ¼ κqÞ, and (iii) κ 1 is the projection of κ on the fundamental (accelerating) mode. In these studies it was tacitly assumed that the maximum gradient applicable is limited by the damage threshold fluence-ignoring beamreduction of the field experienced by the dielectric.…”
Section: System Descriptionmentioning
confidence: 99%
“…2): at the beginning a gradient G 0 is applied, and after the delay time τ D , a ΔG 2 amplitude correction is added for the remainder of the pulse τ B . In both cases, since the wake's nonfundamental modes are suppressed like 1=M 2 [32] we considered only the first dominant mode of the wake ðκ ≃ κ 1 Þ. Figure 2 illustrates the propagating process of five microbunches in two time frames: top frame shows the case when the last bunch enters the structure and the lower frame reveals the conditions when the first bunch exits the interaction region.…”
Section: Laser Pulse Taperingmentioning
confidence: 99%
“…where η 1;max ≡ κ 1 =κ is the single bunch maximum efficiency [29,32,33] determined by the structure-see Table I. Figure 3a shows the train of bunches efficiency normalized to the single bunch maximum efficiency ðη 1;max ¼ 60.5%Þ as a function of the loaded gradient (bottom X-axis) or the structure's geometric length (top X-axis).…”
Section: Self-consistent Analysismentioning
confidence: 99%
“…Previous work on wake effects in DLAs has concentrated on longitudinal effects such as beam loading. This has been described by simplified analytical models of the structures, namely an azimuthal symmetrical and longitudinally flat structure and pointlike bunch distributions [10][11][12][13][14][15]. The analysis of metallic periodically corrugated structures like flat grating-dechirpers [16] has shown that the geometrical parameters influence the wakefields of particles close to the structure.…”
Section: Introductionmentioning
confidence: 99%